2019
DOI: 10.1111/jdv.15498
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia neoplastica as a sign of visceral malignancies: a systematic review

Abstract: Alopecia neoplastica (AN) from visceral tumours is a rare form of cutaneous metastasis in which internal malignancies spread to the scalp. The diagnosis of AN may be very challenging, especially when its onset precedes the diagnosis of the primary tumour. We aimed to improve the knowledge on AN, highlighting that in case of scarring localized alopecia, a differential diagnosis with metastasis should always be considered. We performed a systematic review to describe the main demographic and clinical features as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 117 publications
(1,221 reference statements)
0
21
0
1
Order By: Relevance
“…Macroscopic presentation of each of presented tumor is unspecific, what means that histological examination is required. Differential diagnosis includes BCC, SCC, sebaceous carcinoma, angiosarcoma, clear cell hidradenocarcinoma, other lesions located on the skin, especially other appendageal neoplasms and alopecia neoplastica [ 1 , 37 ]. Dermatoscopy is not recommended for diagnosis because of the unspecific manifestation of each tumor (most lesions have abnormal vascular patterns, areas of calcification, or keratin masses) [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopic presentation of each of presented tumor is unspecific, what means that histological examination is required. Differential diagnosis includes BCC, SCC, sebaceous carcinoma, angiosarcoma, clear cell hidradenocarcinoma, other lesions located on the skin, especially other appendageal neoplasms and alopecia neoplastica [ 1 , 37 ]. Dermatoscopy is not recommended for diagnosis because of the unspecific manifestation of each tumor (most lesions have abnormal vascular patterns, areas of calcification, or keratin masses) [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical markers, such as Ki-67, P53, AE13, AE14, and CD34, may help differentiate PTT with squamous cell carcinoma (SCC) [ 35 , 36 ]. It should be distinguished mainly from other neoplasms, which may be located in this region, and alopecia neoplastica (a rare form of skin metastasis in which internal malignancies spread to the scalp) [ 37 ]. Invasion of the surrounding tissue may be present.…”
Section: Tumors With Follicular Differentiationmentioning
confidence: 99%
“…It was observed that the most common place of the primary tumour was the gastrointestinal tract, followed by breast, kidney, lung, thyroid, uterus, central nervous system, and liver [11]. The authors indicated that in the patients with localized scarring alopecia one always ought to remember about metastatic skin disease [11]. The most frequent site for skin metastasis of RCC has not been found yet.…”
Section: Discussionmentioning
confidence: 99%
“…Compression created in the dermis by tumoral mass itself could compromise survival and development of pilosebaceous units. This would explain the fact that sometimes hair regrew after proper cancer treatment [12,[30][31][32].…”
Section: Pathogenesismentioning
confidence: 99%
“…Attempts have been made to understand if there is a correlation between metastatization to the scalp and the histological type of primitive neoplasia. Few data available seem to highlight that adenocarcinoma is the subtype that most frequently associates with AN, perhaps because of the high density of glands in the scalp [32]. However, adenocarcinoma is the most frequent histologic subtype of breast cancer too.…”
Section: Pathogenesismentioning
confidence: 99%